Multipath characterisation of the MeerKAT core site - Phiri, T.; Davidson, David; Wiid, P. (2017)
© 2017 IEEE. MeerKAT is a precursor o Kilometre Array (SKA) and is present struction in South Africa. When com comprise 64 dishes of 13.5 m, most of concentrated in a 1 km radius. This uration results in a unique multipath whose characteristics must be understo terest of protection against radio frequ ence (RFI). A ray model is applied to propagation through the MeerKAT c mine which orientations of the dishes yi coupling effects and subsequently deriv exponent.